Calcium alginate immobilized TiO2/ZnO beads for the removal of chromium - Shaminie, a/p Ramigam (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Heavy metal contamination in water necessitates exploration of various water treatment technologies. Semiconductor based photocatalysis was studied as a possible mechanism for chromium (Cr) removal. In this study, the calcium alginate immobilized TiO2/ZnO beads were used to remove the Cr from water. The calcium alginate immobilized TiO2/ZnO beads were prepared by mixing the sodium alginate solution and hybrid photocatalysts, titanium dioxide (TiO2) and zinc oxide (ZnO). The calcium alginate beads showed better removal efficiency of Cr in photocatalysis compared to adsorption. The optimum pH for effective Cr removal is pH ~5 which gave about 98.5% of removal efficiency. The removal efficiency of the immobilized photocatalyst was found to be lower than the suspended photocatalyst. However, the immobilized photocatalyst has an advantage in term of reusability which makes them to be an environmentally friendly and cost-effective photocatalyst.